ALGEMENE MIDDELBARE SCHOOL SOLO 1925-1932: PORTRAIT OF THE FIRST MULTICULTURAL EDUCATION IN INDONESIA - Priyatmoko, Heri (History Department, Semarang State University and Historian Society of Indonesia, 2018)
Six decades ago, Muhammad Yamin with some other scholars actualized the dream of Ã¢â‚¬Å“indigenizationÃ¢â‚¬Â of Indonesian historiography in the Indonesian National Historical Seminar I. Yamin obtained the knowledge about Nusantara history when he attended Algemene Middelbare School (AMS) Solo in section A1, Oostersch Letterkundige (Eastern Letter) class. Under the care of Dr. W.F. Stutterheim, archaeologist, AMS students were taught about Indonesian culture. In here, studentsÃ¢â‚¬â„¢ perspective was broadened with the point of views of Islam, Hinduism, and Buddhism since they were taught about Indonesian culture that formed from a mixed element of Islam, Hindu, and Buddhist culture. Not to forget, they also studied Javanese and Malay literature with Raden Tumenggung Yasawidagda. In the era of 1926, it is recorded that this school had more than 100 students. They came from Ambon, Batak, Padang, Aceh, Betawi, Priyangan, Madura, Sumatra, Bali, and Central Java, as well as Chinese and Dutch people. That historical fact shown that AMS Solo was the favorite school at that moment, at least was heard until outside Java. This first school in Indonesia that taught multicultural education produced many magnates at a later time like Dr. Prijono, Dr. Tjan Tjoe Siem, Armijn Pane, Amir Hamzah, Ahdiat K. Mihardja, Prof. Mr. Kusumadi, Prof. Ali Afandi, etc. This paper aims to discuss the learning model in AMS Solo based on cultural diversity, profiles of great teachers in AMS who had produced many national figures, as well as the response of Dutch colonial government and indigenous kingdom.Ã‚Â Enam dekade silam, Muhammad Yamin bersama kaum cerdik pandai lainnya mewujudkan impian Ã¢â‚¬Å“pribumisasiÃ¢â‚¬Â historiografi Indonesia dalam forum Seminar Sejarah Nasional Indonesia I. Pengetahuan tentang sejarah Nusantara diperoleh Yamin tatkala duduk di Algemmene Middelbare School (AMS) Solo. Di sini pula, perspektif siswa diperluas dengan pandangan dari sudut Islam, Hindu, dan Buddha lantaran mereka dicekoki kebudayaan Indonesia yang terbentuk dari percampuran antara unsur budaya Islam, Hindu, dan Buddha. Tidak lupa mempelajari juga kesusasteraan Jawa dan Melayu dengan guru Raden Tumenggung Yasawidagda. Pada era 1926, tercatat sekolahan ini sudah memperoleh murid lebih dari 100 orang. Mereka berasal dari Ambon, Batak, Padang, Aceh, Betawi, Priyangan, Madura, Sumatra, Bali, dan Jawa bagian tengah, serta kelompok Tionghoa dan Belanda. Fakta historis tersebut menujukkan bahwa AMS Solo merupakan sekolah favorit kala itu, setidaknya terdengar sampai ke luar Jawa. Sekolah pertama di Indonesia yang mengajarkan pendidikan multikultural ini melahirkan banyak tokoh terkemuka di kemudian hari seperti Dr. Prijono, Dr Tjan Tjoe Siem, Armijn Pane, Amir Hamzah, Ahdiat K. Mihardja, Prof. Mr. Kusumadi, Prof. Ali Afandi dan lainnya. Makalah ini bertujuan untuk mendiskusikan model pembelajaran di AMS Solo yang berbasis keragaman budaya, profil para guru hebat di AMS yang berhasil menelurkan sederet tokoh bangsa, serta respon pemerintah kolonial Belanda dan kerajaan pribumi.Ã‚Â